Opportunities to Increase the Effectiveness of EHR-Based Diabetes Clinical Decision Support - O‘Connor, P. (Applied Clinical Informatics, 2011)
There are many opportunities to improve diabetes care through more effective use of EHR-based CDS. The report of Kantor et al. [16] is encouraging because it demonstrates sustained efforts by leading health care organizations to implement diabetes-related EHR-based CDS. However, lack of sophisticated treatment-specific CDS and lack of prioritized recommendations are a cause for concern. Even more disturbing is the substantive heterogeneity in content of diabetes CDS recommendations now in the field. Some of CDS recommendations described by Kantor et al. [16] are clearly not evidence-based and could increase costs while not improving clinical benefits. The timely identification of these problems is an awkward but necessary first step towards improvement. The health care organizations that are pioneers in the field should be congratulated and encouraged to continue their collaborative efforts to increase the efficiency and effectiveness of EHR-based CDS. Attending to the modest proposals put forward here and by others may help translate the massive investments that we have made in EHR technology into clinical benefits for our patients.
Keywords: Electronic medical records; clinical decision support; CDS; diabetes; evidence-based medicine; conflict of interest; clinical guidelines